Ice-Dammed Lake Drainage Evolution at Russell Glacier, West Greenland - Carrivick, Jonathan L.; Tweed, Fiona S.; Ng, Felix; Quincey, Duncan J.; Mallalieu, Joseph; Ingeman-Nielsen, Thomas; Mikkelsen, Andreas B.; Palmer, Steven J.; Yde, Jacob C.; Homer, Rachel; Russell, Andrew J.; Hubbard, Alun (Frontiers in Earth Science, 2017)
Glaciological and hydraulic factors that control the timing and mechanisms of glacier lake outburst floods (GLOFs) remain poorly understood. This study used measurements of lake level at fifteen minute intervals and known lake bathymetry to calculate lake outflow during two GLOF events from the northern margin of Russell Glacier, west Greenland. We used measured ice surface elevation, interpolated subglacial topography and likely conduit geometry to inform a melt enlargement model of the outburst evolution. The model was tuned to best-fit the hydrograph’s rising limb and timing of peak discharge in both events; it achieved Mean Absolute Errors of < 5 %. About one third of the way through the rising limb, conduit melt enlargement became the dominant drainage mechanism. Lake water temperature, which strongly governed the enlargement rate, preconditioned the high peak discharge and short duration of these floods. We hypothesize that both GLOFs were triggered by ice dam flotation, and localised hydraulic jacking sustained most of their early-stage outflow, explaining the particularly rapid water egress in comparison to that recorded at other ice-marginal lakes. As ice overburden pressure relative to lake water hydraulic head diminished, flow became confined to a subglacial conduit. This study has emphasised the inter-play between ice dam thickness and lake level, drainage timing, lake water temperature and consequently rising stage lake outflow and flood evolution.